An international, multicenter, prospective study of a prothrombin complex concentrate, Prothromplex Total®, in anticoagulant reversal. Issue 3 (March 2015) - Altorjay, Áron; Szabó, Éva; Boda, Zoltán; Kramer, Ludwig; Ngo, Leock Y.; Engl, Werner; Firth, Clair L.; Ahlstrom, Erik R.; Gelmont, David M.; Pabinger, Ingrid
Abstract Introduction Prothrombin complex concentrates (PCCs) are a common treatment option for the reversal of oral anticoagulation with vitamin K antagonists (VKAs). This study assessed efficacy and safety of Prothromplex Total®. Materials and Methods Patients (≥ 18 years) with acquired prothrombin complex coagulation factor deficiency (international normalized ratio [INR] ≥ 2 at screening) due to oral VKAs, requiring reversal of anticoagulation, were treated with 25, 35, or 50 IU/kg BW PCC. After infusion, efficacy was assessed for 72 ± 4 hours. Adverse events (AEs) were captured for 15 days. Results Sixty-one subjects, 48 requiring interventional procedures and 13 with acute bleeds, received a single infusion of PCC. Of 59 subjects analyzed, all achieved normalization of INR (≤ 1.3) within 30 ± 5 minutes of infusion, demonstrating effective anticoagulant reversal. IVRs of factors II, VII, IX, and X ranged from 1.12-2.03 IU/dL:IU/kg. Median INRs remained between 1.00 and 1.18 for up to 6 hours. Overall efficacy of treatment was rated "excellent" for 60 subjects. Three AEs were deemed possibly related to treatment: 1 serious AE (SAE) of acute myocardial infarction (rated severe), 1 SAE of deep vein thrombosis (rated mild), and 1 AE of pyrexia (rated mild). Thrombotic adverse events (2/61, 3.3%) reported here are comparable to rates observed in other PCC studies. Conclusions While there is a risk of thromboembolic events following treatment with PCC products, the number of events reported here was low and could have occurred without PCC treatment. The individualized, INR-based dosing of PCC used here for VKA anticoagulant reversal produces rapid normalization of INR to ≤ 1.3 within 30 minutes.